1999
DOI: 10.1038/sj.bjc.6690738
|View full text |Cite
|
Sign up to set email alerts
|

31P magnetic resonance spectroscopy as a predictor of efficacy in photodynamic therapy using differently charged zinc phthalocyanines

Abstract: Summary Photodynamic therapy (PDT) is a developing approach to the treatment of solid tumours which requires the combined action of light and a photosensitizing drug in the presence of adequate levels of molecular oxygen. We have developed a novel series of photosensitizers based on zinc phthalocyanine which are water-soluble and contain neutral (TDEPC), positive (PPC) and negative (TCPC) side-chains. The PDT effects of these sensitizers have been studied in a mouse model bearing the RIF-1 murine fibrosarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Since PDT (and more so PDT in combination with HT) is a modality in which a number of treatment parameters related to the photosensitiser and light (drug dose, drug-light interval, light dose, etc) used need to be selected, studies have also been carried out in which magnetic resonance spectroscopy (MRS) techniques have been used to try to predict PDT outcome at the time of treatment. In one such study (Bremner et al, 1999), a clear relationship was seen between MRS measurements of energy metabolism immediately following PDT and the ultimate effect on the tumour in terms of regrowth delay. The data obtained in the present study would also support the concept that monitoring of ATP or lactate levels may provide information on the effectiveness of PDT-based treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Since PDT (and more so PDT in combination with HT) is a modality in which a number of treatment parameters related to the photosensitiser and light (drug dose, drug-light interval, light dose, etc) used need to be selected, studies have also been carried out in which magnetic resonance spectroscopy (MRS) techniques have been used to try to predict PDT outcome at the time of treatment. In one such study (Bremner et al, 1999), a clear relationship was seen between MRS measurements of energy metabolism immediately following PDT and the ultimate effect on the tumour in terms of regrowth delay. The data obtained in the present study would also support the concept that monitoring of ATP or lactate levels may provide information on the effectiveness of PDT-based treatments.…”
Section: Discussionmentioning
confidence: 99%
“…NMR data analysis revealed significant differences in the time course of changes in high energy phosphate levels in response to combined hyperthermia and photodynamic therapies [29]. It was also demonstrated that there is a relationship between NMR measurements immediately following PDT and the ultimate effect on the tumor [26]. Third, diffusion-weighted MRI showed a biphasic change in the apparent diffusion coefficient (ADC) within the first 24 hours post-PDT, indicating the early response of PC-14 tumors to PDT [11].…”
Section: Introductionmentioning
confidence: 93%
“…Gadolinium diethylenetriamene pentaacetate (DTPA) contrast-enhanced MRI was used to assess the boundary of PDT-induced tissue necrosis in a canine model [23] and in human patients [24]. Second, in vivo 31 P nuclear magnetic resonance (NMR) spectroscopy has been used to monitor tumor metabolic status before and after the treatment of RIF-1 tumors [25,26] and mammary carcinoma [27][28][29][30]. NMR data analysis revealed significant differences in the time course of changes in high energy phosphate levels in response to combined hyperthermia and photodynamic therapies [29].…”
Section: Introductionmentioning
confidence: 99%
“…The development of noninvasive means of implicit or explicit treatment dosimetry in PDT has expanded in recent years with reports on singlet oxygen monitoring (55), NADH fluorescence monitoring (56), 31 P magnetic resonance spectroscopy (57,58), and BOLD-contrast magnetic resonance imaging (59) providing evidence of potential utilization of each technique in PDT. Broadband reflectance spectroscopy is based on the diffusion model and photon migration inside scattering media, similar to near-infrared photon-migration spectroscopy reported by Pham et al (21).…”
Section: Oxygen Measurement and Photodynamic Therapy Outcomementioning
confidence: 99%